Patterns and trends of atmospheric mercury in the GMOS network: Insights based on a decade of measurements - Mariantonia Bencardino; Francesco D’Amore; Hélène Angot; Lorenzo Angiuli; Yann Bertrand; Warren Cairns; María C. Diéguez; Aurélien Dommergue; Ralf Ebinghaus; Giulio Esposito; Kateřina Komínková; Casper Labuschagne; et al. (Environmental Pollution, 2024)

Low pH adaptation of tropical exotic acid tolerance yellow maize donor lines in sub-tropical breeding programs - Dibanzilua Nginamau; Casper Nyaradzai Kamutando; Cosmos Magorokosho; João Constâncio Saraiva; Angeline van Biljon; Maryke Labuschagne (Euphytica, 2024)
Soil acidity is one of the most important constraints to maize production in Angola, where both yellow and white maize is essential for food and feed requirements. In this study, four yellow acid soil tolerant donor lines from the International Maize and Wheat Improvement Centre (CIMMYT)—Colombia were crossed with ten yellow elite lines adapted to the mid-altitude climatic conditions developed by CIMMYT—Zimbabwe, in order to identify donor lines, which can be potential sources of acid tolerance genes in breeding programs in Angola and within the mid-altitude climatic zones. The two groups of parents were crossed using a line by tester mating design, yielding 36 crosses with sufficient seed, which were evaluated alongside six acid tolerant commercial hybrids, during the 2014–16 cropping seasons at nine sites, representing acid and non-acid soils in Angola and Zimbabwe. A significant ( p < 0.05) line and line × tester effect for grain yield performance was observed across acid and non-acid conditions. Acid tolerance donor lines CY3 and CY1 showed the highest positive GCA effects for grain yield. In addition, crosses involving these two donor lines had the best yielding ability and stability under both acid and non-acid conditions. For instance, the crosses CH142464 (ZY2 × CY3) and, CH142447 (ZY2 × CY1) were the best combinations for grain yield performance under both acid and non-acid soil conditions, and were stable compared to the commercial check hybrids. Crosses involving the acid tolerant donor lines mostly flowered earlier than the commercial checks. Overall, the data showed the potential of tropically-adapted exotic yellow maize acid tolerance donor lines in improving productivity of sub-tropical maize under both low-pH and well-managed soil conditions.

A synthesis of mercury research in the Southern Hemisphere, part 2: Anthropogenic perturbations - Jenny A. Fisher; Larissa Schneider; Anne-Hélène Fostier; Saul Guerrero; Jean Remy Davée Guimarães; Casper Labuschagne; Joy J. Leaner; Lynwill G. Martin; Robert P. Mason; Vernon Somerset; Chavon Walters (Ambio, 2023)
Environmental mercury (Hg) contamination is a global concern requiring action at national scales. Scientific understanding and regulatory policies are underpinned by global extrapolation of Northern Hemisphere Hg data, despite historical, political, and socioeconomic differences between the hemispheres that impact Hg sources and sinks. In this paper, we explore the primary anthropogenic perturbations to Hg emission and mobilization processes that differ between hemispheres and synthesize current understanding of the implications for Hg cycling. In the Southern Hemisphere (SH), lower historical production of Hg and other metals implies lower present-day legacy emissions, but the extent of the difference remains uncertain. More use of fire and higher deforestation rates drive re-mobilization of terrestrial Hg, while also removing vegetation that would otherwise provide a sink for atmospheric Hg. Prevalent Hg use in artisanal and small-scale gold mining is a dominant source of Hg inputs to the environment in tropical regions. Meanwhile, coal-fired power stations continue to be a significant Hg emission source and industrial production of non-ferrous metals is a large and growing contributor. Major uncertainties remain, hindering scientific understanding and effective policy formulation, and we argue for an urgent need to prioritize research activities in under-sampled regions of the SH.

Identification of exotic temperate maize inbreds for use in tropical breeding programs - Ozwell Ndoro; Cosmos Magorokosho; Peter S. Setimela; Casper N. Kamutando; Maryke T. Labuschagne (Euphytica, 2022)